Addictions Diagnosis and Treatment - Meil, William M.; Mills, John A. (IntechOpen, 2021)
This book addresses the diagnosis and treatment of drug addiction. Chapters in this book span biological, psychological, cultural, and health-based perspectives and emphasize meeting people as they really are in order to obtain tangible advances in clinical practice. These works represent the integration of the past, present, and likely future directions of both diagnosis and treatment. Addiction is an individual and systemic challenge to society and scientific advances and cultural diversity are highlighted here as paths forward towards addressing current diagnostic and treatment obstacles.